A comparative study of the efficacy and safety of Phacoemulsifacation in white mature and other types of senile cataracts - kumar Meena, Ravindra; Chouhan, J K; Sharma, Pankaj; Meena, Ashok; Sharma, Devesh (International Journal of Medical Research and Review, 2015)
Introduction: Phacoemulsification in white mature cataract is one of the most difficult anterior segment procedure. Our purpose to conduct this study was to compare the outcome of Phacoemulsification in white mature and other type (immature cortical, nuclear, posterior subcapsular and mixed cataract) of senile cataract. Methods: This is a hospital based observational Study conducted on 100 patients of cataract (49 male and 51 female) in the upgraded department of Ophthalmology, SMS Medical college Jaipur subjected to clear corneal temporal phacoemulsification with foldable IOL. Postoperative outcome, intraoperative difficulties were analyzed between two groups. Postoperative examination were done at 1st, 3rd, 7th, 30th & 45thday. Results: Intraoperative difficulties, postoperative corneal oedema, mean IOP changes & postoperative BCVA were not significantly different between two groups (p>0.05). Mean effective phaco time between two groups was found to be significantly higher in white mature cataract group (p<0.01). Conclusion: The Phacoemulsification is equally safe and efficacious in white mature senile cataracts as in other senile cataracts.